Scientometric Analysis of Research on Information and Library Policy - S. V. Sokolov (Библиосфера)
The article presents tools for searching and analyzing keywords in the scientific electronic library eLIBRARY.ru. On the basis of identifying common keywords in research on information and library policy, as well as determining of the most used keywords in each of the scientific areas, the current state and prospects for the integration of library science, political science and sociological research are determined. The author comes to the following conclusions. The most important topics are related to such keywords as “information resources”, “information equality”, “information space”; library studies on the issues of state regulation of the development of the media space and the promotion of news information have not been recorded, there are very few studies on the actualization of libraries as subjects of the promotion of state civilizational values.